Neutralizing activity against Omicron BA.5 after tixagevimab/cilgavimab administration comparable to those after Omicron BA.1/BA.2 breakthrough infections - Yang, Jinyoung; Won, Gunho; Baek, Jin Yang; Lee, Young Ho; Kim, Haein; Huh, Kyungmin; Cho, Sun Young; Kang, Cheol-In; Chung, Doo Ryeon; Peck, Kyong Ran; Lee, Kyo Won; Park, Jae Berm; et al. (Frontiers in Immunology, 2023)
Introduction: The effect of tixagevimab/cilgavimab (EvusheldTM; AstraZeneca, UK) should be evaluated in the context of concurrent outbreak situations. Methods: For serologic investigation of tixagevimab/cilgavimab during the BA.5 outbreak period, sera of immunocompromised (IC) hosts sampled before and one month after tixagevimab/cilgavimab administration and those of healthcare workers (HCWs) sampled one month after a 3rd shot of COVID-19 vaccines, five months after BA.1/BA.2 breakthrough infection (BI), and one month after BA.5 BI were investigated. Semi-quantitative anti-spike protein antibody (Sab) test and plaque reduction neutralizing test (PRNT) against BA.5 were performed. Results: A total of 19 IC hosts (five received tixagevimab/cilgavimab 300 mg and 14 received 600 mg) and 41 HCWs (21 experienced BA.1/BA.2 BI and 20 experienced BA.5 BI) were evaluated. Baseline characteristics did not differ significantly between IC hosts and HCWs except for age and hypertension. Sab significantly increased after tixagevimab/cilgavimab administration (median 130.2 BAU/mL before tixagevimab/cilgavimab, 5,665.8 BAU/mL after 300 mg, and 10,217 BAU/mL after 600 mg; both P < 0.001). Sab of one month after the 3rd shot (12,144.2 BAU/mL) or five months after BA.1/BA.2 BI (10,455.8 BAU/mL) were comparable with that of tixagevimab/cilgavimab 600 mg, while Sab of one month after BA.5 BI were significantly higher (22,216.0 BAU/mL; P < 0.001). BA.5 PRNT ND50 significantly increased after tixagevimab/cilgavimab administration (median ND50 29.6 before tixagevimab/cilgavimab, 170.8 after 300 mg, and 298.5 after 600 mg; both P < 0.001). The ND50 after tixagevimab/cilgavimab 600 mg was comparable to those of five months after BA.1 BI (ND50 200.9) while ND50 of one month after the 3rd shot was significantly lower (ND50 107.6; P = 0.019). The ND50 of one month after BA.5 BI (ND50 1,272.5) was highest among tested groups, but statistical difference was not noticed with tixagevimab/cilgavimab 600 mg. Conclusion: Tixagevimab/cilgavimab provided a comparable neutralizing activity against the BA.5 with a healthy adult population who were vaccinated with a 3rd shot and experienced BA.1/BA.2 BI.